Translators’ Choices in Tartuffe - Senior, Nancy (TTR)

(untitled) (Association canadienne de traductologie, 2001)
AbstractSelected passages from twelve English translations of Molière’s Tartuffe are studied. The passages are chosen because of questions they raise about the language of everyday life and of religion in seventeenth-century France. The translators choose the extent to which they will keep the structures and references of the original text, or adapt them for easier access by a contemporary audience. They also choose between the French tradition of a dark, menacing interpretation, and the North American one of seeking the maximum of laughs.